What is the cost of integration? Evidence from an integrated health and agriculture project to improve nutrition outcomes in Western Kenya - Levin, C.; Self, J.; Kedera, E.; Wamalwa, M.; Hu, J.; Grant, F.; Girard, Amy W.; Cole, Donald C.; Low, Jan W. (Oxford University Press, 2019)
Integrated nutrition and agricultural interventions have the potential to improve the efficiency and effectiveness of investments in food security and nutrition. This article aimed to estimate the costs of an integrated agriculture and health intervention (Mama SASHA) focused on the promotion of orange-fleshed sweet potato (OFSP) production and consumption in Western Kenya. Programme activities included nutrition education and distribution of vouchers for OFSP vines during antenatal care and postnatal care (PNC) visits. We used expenditures and activity-based costing to estimate the financial costs during programme implementation (2011–13). Cost data were collected from monthly expense reports and interviews with staff members from all implementing organizations. Financial costs totalled US$507 809 for the project period. Recruiting and retaining women over the duration of their pregnancy and postpartum period required significant resources. Mama SASHA reached 3281 pregnant women at a cost of US$155 per beneficiary. Including both pregnant women and infants who attended PNC services with their mothers, the cost was US$110 per beneficiary. Joint planning, co-ordination and training across sectors drove 27% of programme costs. This study found that the average cost per beneficiary to implement an integrated agriculture, health and nutrition programme was substantial. Planning and implementing less intensive integrated interventions may be possible, and economies of scale may reduce overall costs. Empirical estimates of costs by components are critical for future planning and scaling up of integrated programmes.